Physiologically based pharmacokinetic modeling to predict the effect of risperidone on aripiprazole pharmacokinetics in subjects with different CYP2D6 genotypes and individuals with hepatic impairment - Fan Mou; Zhiwei Huang; Yu Cheng; Xue Zhao; Xiujia Sun; Huafang Li; Shunying Yu (Therapeutic Advances in Drug Safety)
Background: Aripiprazole and risperidone, widely used atypical antipsychotics, are commonly adjunctively prescribed in clinical practice. When aripiprazole was combined with risperidone, the genotype of drug-metabolizing enzymes and liver impairment may lead to complex pharmacokinetic changes. The Physiologically Based Pharmacokinetic (PBPK) model can predict the influence of these factors on plasma concentration and optimize dosage regimens. Objectives: This study aims to investigate the pharmacokinetic changes of aripiprazole caused by various influencing factors when it was co-administered with risperidone through PBPK models. Design: The PBPK models of aripiprazole and risperidone were developed by gathering physicochemical parameters and drug-specific parameters. Then, by combining the inhibitory parameters, the enzymatic kinetic parameters of CYP2D6 genotypes, and the changes in anatomical and physiological parameters when liver function is damaged, the corresponding PBPK models were further established. Finally, this study put forward dosage optimization recommendations for situations where risks may exist. Methods: The comparison between predicted and observed plasma concentration data, along with the assessment of pharmacokinetic parameters, was utilized to evaluate the fit performance of the models. Results: The simulations of the PBPK model revealed that co-administration of risperidone did not result in significant changes in aripiprazole pharmacokinetics. However, in individuals with mild hepatic impairment and CYP2D6 normal metabolizer, a dose reduction of approximately 11% was advised when aripiprazole was combined with risperidone. When individuals with mild liver damage have CYP2D6 genotypes of intermediate metabolizer (IM) and poor metabolizer (PM), aripiprazole doses should be further reduced to 61% and 51%, respectively. Conclusion: The co-administration of aripiprazole and risperidone is generally considered safe from a pharmacokinetic perspective. However, if individuals have a CYP2D6 genotype of IM or PM and/or if they have mild hepatic impairment, adjusting the dose of aripiprazole is advisable to mitigate potential risks when combining it with risperidone.